A new species of Teagueia (Orchidaceae: Pleurothallidinae) from Northern of Peru - Chocce, Miguel (2011)
A new species of Teagueia (Luer) Luer (Orchidaceae: Pleurothallidinae) from the highlands of Northern Peru is described and illustrated with a black and white drawing. This species is the first record of genus Teagueia (Luer) Luer in Peru.